Impact of Leadership Style and Perceived Organizational Support on the Organizational Citizenship Behaviour of Librarians in Indian Universities - Mahendiren, Dinesh Babu; Kushwaha, Bijay Prasad (Indian Journal of Information Sources and Services, 2023)
This paper aims to analyse the Organizational Citizenship Behaviour (OCB) of librarian employees in Indian university. Further, with the support of the organization and the transformational leadership style (TL) how the employee perceives their values and replicate them in the organization. This study reveals the influence of the social exchange theory on employee reciprocity and behaviour. Transformational leadership enhance the citizenship behaviour of librarian in the university and the employee perceive that the organizational support (POS) their initiation and decision they reciprocally show their citizenship behaviour. The data was received from 121 university librarians at an Indian institution. To analyse the structural relationships in the study framework, a partial least squares approach was employed. The findings show that TL has a positive impact on organisational citizenship behaviour, and POS mediates the impact of organisational citizenship and transformational leadership. Furthermore, when organisations and leaders encourage and value their employees’ efforts, the employee exhibit citizenship behaviours in the organisation. The theoretical and practical implications are discussed.